The Importance and Implementation of National Tourism Branding - Mohamad Fidelio Omar (Eduvest - Journal of Universal Studies, 2026)
The objective of this academic research paper is to provide more information, knowledge, as well as a new perspective regarding the importance of a Branding for a country, especially in terms of tourism sector. In addition, this academic research paper also aims to help the Indonesian Government, business people, Organizations, and Indonesian society, to be more struggle and work hard in promoting tourism industry in Indonesia. This academic research paper was using primary research, one of the ways was by spreading online questionnaire to some respondents at IMI University Centre Switzerland and also in Indonesia, covering female and male. Questionnaire in general which related with Branding, Marketing Activities, Consumer Behavior, Communication, and Indonesia. In accordance to the results from the survey questionnaire that Indonesia was already well known in the international market. Besides that, the Internet is a very useful as marketing tools to promote tourism products. However, all Indonesian people still need to work hard in terms of promoting and performing good management order to increase the number of foreign tourists to visiting Indonesia. This academic research project expected to be useful for many people, such as the Indonesian Government, Business People, Organization, and Local People in the process of developing tourism industry in Indonesia. Because, actually Indonesia has a lot of potentials to be continue to grow in terms of Tourism Industry.